A case study of global health at the university: implications for research and action - Andrew D. Pinto; Donald C. Cole; Aleida ter Kuile; Lisa Forman; Katherine Rouleau; Jane Philpott; Barry Pakes; Suzanne Jackson; Carles Muntaner (Taylor & Francis Group, 2014)
Background: Global health is increasingly a major focus of institutions in high-income countries. However, little work has been done to date to study the inner workings of global health at the university level. Academics may have competing objectives, with few mechanisms to coordinate efforts and pool resources. Objective: To conduct a case study of global health at Canada's largest health sciences university and to examine how its internal organization influences research and action. Design: We drew on existing inventories, annual reports, and websites to create an institutional map, identifying centers and departments using the terms 'global health' or 'international health' to describe their activities. We compiled a list of academics who self-identified as working in global or international health. We purposively sampled persons in leadership positions as key informants. One investigator carried out confidential, semi-structured interviews with 20 key informants. Interview notes were returned to participants for verification and then analyzed thematically by pairs of coders. Synthesis was conducted jointly. Results: More than 100 academics were identified as working in global health, situated in numerous institutions, centers, and departments. Global health academics interviewed shared a common sense of what global health means and the values that underpin such work. Most academics interviewed expressed frustration at the existing fragmentation and the lack of strategic direction, financial support, and recognition from the university. This hampered collaborative work and projects to tackle global health problems. Conclusions: The University of Toronto is not exceptional in facing such challenges, and our findings align with existing literature that describes factors that inhibit collaboration in global health work at universities. Global health academics based at universities may work in institutional siloes and this limits both internal and external collaboration. A number of solutions to address these challenges are proposed.